2018
DOI: 10.1039/c8nr00108a
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature synthesis of 2D MoS2on a plastic substrate for a flexible gas sensor

Abstract: The efficient synthesis of two-dimensional molybdenum disulfide (2D MoS2) at low temperatures is essential for use in flexible devices. In this study, 2D MoS2 was grown directly at a low temperature of 200 °C on both hard (SiO2) and soft substrates (polyimide (PI)) using chemical vapor deposition (CVD) with Mo(CO)6 and H2S. We investigated the effect of the growth temperature and Mo concentration on the layered growth by Raman spectroscopy and microscopy. 2D MoS2 was grown by using low Mo concentration at a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 48 publications
3
119
0
2
Order By: Relevance
“…Devices based on SiNMs were shown to withstand bending radii down to 5 mm for a strain of 0.025% [217]. Similarly to graphene, transition metal dichalcogenides (TMDs), namely MoS 2 [234][235][236][237][238][239][240][241][242], WS 2 [243][244][245][246], and WSe 2 [247][248][249], were employed in the fabrication of flexible sensors due to their mechanical and electrical properties when scaled down to a single or few 2D crystalline layers. Among these materials, MoS 2 is the most widely used due to its widespread availability [250].…”
Section: Flexible Siliconmentioning
confidence: 99%
See 1 more Smart Citation
“…Devices based on SiNMs were shown to withstand bending radii down to 5 mm for a strain of 0.025% [217]. Similarly to graphene, transition metal dichalcogenides (TMDs), namely MoS 2 [234][235][236][237][238][239][240][241][242], WS 2 [243][244][245][246], and WSe 2 [247][248][249], were employed in the fabrication of flexible sensors due to their mechanical and electrical properties when scaled down to a single or few 2D crystalline layers. Among these materials, MoS 2 is the most widely used due to its widespread availability [250].…”
Section: Flexible Siliconmentioning
confidence: 99%
“…Based on the methods developed for the deposition of graphene, MoS 2 has been implemented in flexible substrates using mechanical [239], and chemical exfoliation [234,241,254,255]. In addition, other methods such as CVD on SiO 2 followed by transfer of the nanoflakes [235][236][237], PECVD [256], sulfurisation of Mo film [257], and more recently the direct hydrothermal growth of MoS 2 on aluminium foil were researched [238]. In flexible sensors, TMDs are mostly used as sensitive layers in gas sensors, and multiple reviews can be found on the subject [250,258,259].…”
Section: Flexible Siliconmentioning
confidence: 99%
“…Lee et al prepared MoS 2 film by sulfurizing a thin layer of Mo and used it for sensing ammonia in concentration range of 2–30 ppm with an empirical limit of detection of 300 ppb 160. Zhao et al used a CVD technique with precursors like Mo(CO) 6 and H 2 S to grow MoS 2 film both on hard (SiO 2 ) and soft (polyimide) substrate at low temperature (i.e., 200 °C) for ammonia and NO 2 sensor 161. A comparative performance of flexible sensor towards NO 2 and NH 3 showed much better results toward NO 2 gas (a response of ≈300% at 5 ppm) as compared to NH 3 (a response of only 5% at 5 ppm) gas.…”
Section: Molybdenum Chalcogenides and Their Sensing Applicationsmentioning
confidence: 99%
“…One strategy to realize accurate measurements at low temperatures is based on the nanostructure design of 2D metal oxide nanostructures. 7,8 However, progress in the eld of functionalized nanostructure design has not conformed to expectations and the structural design of high-performance sensing materials at low temperatures (even below the freezing point) still remains a challenging task.…”
Section: Introductionmentioning
confidence: 99%